Postoperative Care for Caesarean Patients with Anemia: Case Study at Kardinah Hospital Tegal - Mariska Nurlatifah; Ema Wahyu Ningrum (Buletin Ilmu Kebidanan dan Keperawatan, 2025)
C aesarean section (CS) and experiencing preeclampsia and mild anemia, showing unstable vital signs and low haemoglobin levels (9.8 g/dL). After implementing nursing interventions over three days, including non-pharmacological techniques to reduce pain and increase breast milk production, this case report describes the nursing care provided to Mrs. B, a 32-year-old patient admitted to the Mawar Antenatal Ward at Kardinah Hospital in Tegal. She experienced a significant reduction in pain and improved mobility. The average pain level using the Numeric Rating Scale (NRS) decreased from 7.0 on the first day to 5.5 on the second day, with 60% of patients still reporting bothersome pain. These results indicate that comprehensive pain management and anemia management are crucial for improving the quality of recovery in patients following a caesarean section. The descriptive case study method included physical assessment, laboratory data, and medical records. Nursing diagnoses: acute pain, ineffective breastfeeding, and impaired physical mobility.